Go Mental Healthy Mental Health Services Based on Mobile App To Address Problems In Online Learning In The Covid-19 Pandemic - Umi ba'dingatul Latifah; Atni Dwi Hasmara Yekti; Tiyas Akbar Wahyu Satria; Mellysa Yulinar Yulinar; Viona Rizqy Ananda; Shubhi Mahmashony Harimurti (IJCER (International Journal of Chemistry Education Research), 2023)
During the Covid-19 pandemic, SMA Negeri 1 Cangkringan was one of the schools that implemented online learning methods. However, in practice, there are many obstacles experienced by students such as students feeling heavy and difficulty understanding the material, piling up assignments received by students, the emergence of fear in students about their academic progress, a sense of failure in achieving the expected targets, pressure to be able to learn independently, demands high concentration in paying attention to the teacher's explanation during the learning process which is often constrained by signals so that the teacher's voice is not heard by students, tired and worried about piling up assignments, pressure from parents, and students are not used to the assignment deadline. This condition makes students stressed with their academic life. Therefore, the Gotalty application was developed as a medium for educators to identify problems in online learning faced by students and assist students in maintaining a balance between psychological conditions and academic conditions during the learning process. The program implementation method is carried out by applying the PDCA method (Plan, Do, Check, and Action). The results obtained based on the program that has been carried out, namely the Gotalty application can help relieve anxiety about the problems experienced by students during online learning, and increase students' knowledge of mental health which shows that the psychoeducation process has been successfully carried out, and increases awareness of mental health. Very helpful features for program partners are motivational videos and psychology articles. This is evidenced by the results of the pretest and post-test. In addition, this program also produces outputs in the form of program implementation guidebooks, partner pocketbooks, and program implementation videos.